2009
DOI: 10.1523/jneurosci.4694-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Attributes of Complex Tasting Divalent Salts Are Mediated by TRPM5 and TRPV1 Channels

Abstract: Complex tasting divalent salts (CTDS) are present in our daily diet, contributing to multiple poorly understood taste sensations. CTDS evoking metallic, bitter, salty, and astringent sensations include the divalent salts of iron, zinc, copper, and magnesium. To identify pathways involved with the complex perception of the above salts, taste preference tests (two bottles, brief access) were performed in wild-type (WT) mice and in mice lacking (1) the T1R3 receptor, (2) TRPV1, the capsaicin receptor, or (3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 49 publications
(82 reference statements)
1
37
0
Order By: Relevance
“…TRPM5 is a highly temperature sensitive, heat activated channel, which has a key role in the perception of sweet, umami and bitter taste (Talavera, et al, 2005, Talavera, et al, 2007. However, studies show that metallic taste is unlikely to be activated by TRPM5 (Riera, et al, 2009), indicating that TRPM5 may not be the only potential mechanism for 'phantom taste' and that further research is needed to determine the mechanisms involved.…”
Section: Thermal Stimulation Of Tastementioning
confidence: 99%
“…TRPM5 is a highly temperature sensitive, heat activated channel, which has a key role in the perception of sweet, umami and bitter taste (Talavera, et al, 2005, Talavera, et al, 2007. However, studies show that metallic taste is unlikely to be activated by TRPM5 (Riera, et al, 2009), indicating that TRPM5 may not be the only potential mechanism for 'phantom taste' and that further research is needed to determine the mechanisms involved.…”
Section: Thermal Stimulation Of Tastementioning
confidence: 99%
“…'New' taste qualities and the chemical sense Besides bitter, sweet, umami, sour, and salty, several new taste qualities have been identified, such as the taste of minerals, which may arise from the TRPV1 (transient receptor potential cation channel subfamily V member 1) receptor [79,80] or the taste of calcium, arising from a heterodimer of T1R3 and the calcium-sensing receptor [81]. Humans also perceive chemicals such as menthol (cool) or capsaicin (chili hot).…”
Section: Differences In Umami Sour and Salty Taste Detectionmentioning
confidence: 99%
“…However, the role of TRPM5 is by no means restricted to the sensing of sweet, bitter, and umami taste. It is suggested that the sensory attributes of complex-tasting divalent salts are also mediated by TRPM5 and TRPV1 channels (42). TRPM5 is also essential for fat taste (23) and for linoleic acid-induced CCK secretion from the enteroendocrine cell line STC-1 (44).…”
mentioning
confidence: 99%